A Daoist Pedagogy Encountering New Materialism in Art Education. (3rd July 2021) - Shin, Ryan; Yang, Xuhao
Abstract : In this article, we explore three Daoist concepts in East Asian historical and cultural contexts, addressing Daoism and its educational significance in connecting with new materialism theory. We argue that Daoism's nonaction, the interdependence of things and concepts, and nonlinguistic learning allow us to expand art education from the Cartesian focus on the mind to a balanced art education practice of including affects and nonlinguistic ways of exploration. We also provide suggestions for art education pedagogy and practice reflecting on both Daoism and new materialism's theoretical constructs.